2020
DOI: 10.3390/en13174383
|View full text |Cite
|
Sign up to set email alerts
|

Do Energy Resource Curse and Heterogeneous Curse Exist in Provinces? Evidence from China

Abstract: This study aims to find the relationship between energy resource dependence and economic growth in consideration of interprovincial heterogeneity. This paper first uses panel data from 14 provinces with rich energy resources in China between 2001 and 2016 as a whole to test the energy resource curse hypothesis. It finds that there is no obvious resource curse from a general perspective. It further makes time prediction and transmission channel analysis based on regressions of each province and classifies them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Scholars who hold the view of the "resource curse" posit that abundant natural resources are a curse but not a driver of economic development [10,11]. Their reasons can be summarized in three aspects: the squeezing effect, deteriorating trade terms, and the weakening of the political system.…”
Section: Literature Review and Theoretical Mechanism 21 Resource Endo...mentioning
confidence: 99%
“…Scholars who hold the view of the "resource curse" posit that abundant natural resources are a curse but not a driver of economic development [10,11]. Their reasons can be summarized in three aspects: the squeezing effect, deteriorating trade terms, and the weakening of the political system.…”
Section: Literature Review and Theoretical Mechanism 21 Resource Endo...mentioning
confidence: 99%
“…The results are supported by Hu et al (2020), who demonstrated that the resource curse in the Chinese province of Xinjiang is caused mainly by the dependence on energy resources of about 63% and 37% by other transmission channels such as education, level of nationalisation and investment.…”
Section: Source: Calculated By Authormentioning
confidence: 67%
“…Government of such a country invests more in national security (Military) and exclusively supports its ethnic group to protect its interests in the resource-rich geographic region (Ross, 2001). Hu et al (2020) found that fixed-asset investment is negatively correlated with energy resources in six provinces of China and positive with economic growth. Thus, confirming the transmission channel through the productive expenditure channel.…”
Section: Identification Of Transmission Channels Of the Resource Cursementioning
confidence: 99%
“…Based on extant study in the literature of resource curse ( Atkinson and Hamilton, 2003 ; Fleming et al, 2015 ; Perez-Sebastian and Raveh, 2016 ; Corrocher et al, 2020 ; Hu et al, 2020 ), this study constructs an empirical model of the influence factors of the cultural industries, which covering cultural resources, and empirically examines the influence effect of cultural resources on the cultural industries by region. In this model, the added value of the cultural industries is taken as the explained variable, cultural resources as the core explanatory variable, and control variables covering cultural industries input factors, cultural institutional mechanism factors, and economic environmental factors.…”
Section: Methodsmentioning
confidence: 99%